Genre and openness in Proverbs 10:1-22:16 - Millar, Suzanna R. (Ancient Israel and Its Literature Ser., 2020)
"In Genre and Openness in Proverbs 10:1-22:16, Suzanna R. Millar argues that the sayings in these chapters are a hybrid genre of didactic proverb. These sayings train a student's mind by opening up a number of complex possible interpretations while being multifunctional and widely applicable. By incorporating paremiology, the technical study of the proverb genre, Millar sheds light on important issues within these chapters, including character development, the connection between act and consequence, and the acquisition of wisdom"--